Active Involvement of People with Disabilities in Education: A Literature Review - Milot, Élise; Ruest-Paquette, Anne-Sophie; Fortin, Gabrielle; Letscher, Sylvain; Dogba, Maman Joyce (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2018)
In recent years, a growing number of educational initiatives designed for current and future professionals have sought the active involvement of patients and users. Recent reviews have explored different aspects of these initiatives. However, they do not distinguish between the involvement of people with disabilities and that of other users. This review describes the main features of educational initiatives in the fields of education, health and social sciences that actively seek the involvement of people with disabilities. Our systematic approach identified 20 projects. We analyzed their nature, the actors involved, and their documented outcomes. This review shows that to improve professional practice and the quality of services given to people with disabilities, it is important to seek their active participation in educational initiatives targeting learners from a range of disciplines and to use a diversity of teaching strategies. Recommendations to consider when implementing such initiatives are also discussed.